Financial Literacy and Financial Management on Access to Financing for Small and Medium Enterprises: Moderation of Securities Crowdfunding - Dandi Juana; Rizqi Khalda Suryanto; Abdul Haris (Indonesian Journal of Business Analytics, 2024)
Small and medium enterprises (SMEs) are an important sector in the Indonesian economy. Ease of access to financing is a major factor for growth. This study aims to analyze the relationship between financial literacy, financial management, securities crowdfunding, and access to SME financing. Data were obtained from 100 SMEs in Cirebon City through questionnaires and using the Structural Equation Modeling (SEM) method on the basis of Partial Least Squares (PLS). The results showed that financial literacy and financial management have a significant positive influence on SMEs' access to financing. However, securities crowdfunding does not have a significant influence on SMEs' access to finance. In addition, securities crowdfunding also moderates the relationship between financial management and financial literacy with access to SME financing. This research contributes to the importance of increasing financial literacy and financial management in supporting the growth and progress of SMEs, as well as how securities crowdfunding influences SME financing alternatives.